2015
DOI: 10.4103/0366-6999.155085
|View full text |Cite
|
Sign up to set email alerts
|

Values of the Wells and Revised Geneva Scores Combined with D-dimer in Diagnosing Elderly Pulmonary Embolism Patients

Abstract: Background:Pulmonary embolism (PE) can be difficult to diagnose in elderly patients because of the coexistent diseases and the combination of drugs that they have taken. We aimed to compare the clinical diagnostic values of the Wells score, the revised Geneva score and each of them combined with D-dimer for suspected PE in elderly patients.Methods:Three hundred and thirty-six patients who were admitted for suspected PE were enrolled retrospectively and divided into two groups based on age (≥65 or <65 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…We identified 12 studies [10][11][12][13][14][15][16][18][19][20][21][22] with 3613 patients that met our inclusion criteria for meta-analysis. The detailed steps of our literature search are shown in Fig.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 12 studies [10][11][12][13][14][15][16][18][19][20][21][22] with 3613 patients that met our inclusion criteria for meta-analysis. The detailed steps of our literature search are shown in Fig.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Many studies have investigated the accuracy of these two rules for diagnosis the PE. However, some studies believed the Wells score is more accurate for clinical predicting acute PE than the modified Geneva score [10][11][12], some studies believed the revised Geneva score is equivalent to the Wells rule [13][14][15], while Guo et al believed Wells score is more accurate than the modified Geneva score in nonelderly patients, but not in elderly patients [16]. These conclusions were controversial, and many studies have small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…In a metaanalysis, it was found that Wells score was better than Revised Geneva score in PE exclusion [15]. In another study, Wells score was found to be more successful in detecting PE than Revised Geneva Score in elderly patients; the use of d-dimer test together was shown to increase success rates in two scores [16]. Cheng et al reported that using Wells score with D-dimer test was more successful than Revised Geneva score with D-dimer test to determine the success of PE detection [17].…”
Section: Discussionmentioning
confidence: 98%
“…48 Besides, research results indicate that in older, high-risk patients, the Wells scores are more in correlation with the diagnosis of PE than the revised Geneva score. [49][50][51] The D-dimer values significantly aided the physicians' decision to refer the patient to further hospital treatment under the diagnosis of PE. When D-dimer values were < 0.5 mg/L, twothirds of patients were not referred for further hospital treatment and the others were referred under some other diagnosis.…”
Section: Discussionmentioning
confidence: 99%